A cross sectional study on menstrual hygiene practices among the village women attending a primary health centre, Tripura - Das, Dilip Kumar; Chakraborty, Tamal; Chakraborty, Saumik; Tripura, Kaushik; Datta, Arindam; Pal, Anuranjita (International Journal Of Community Medicine And Public Health, 2019)
Background: Hygienic practices performed by the rural women during menstrual cycle is often remain unsatisfactory, resulting adverse health outcomes and poor productivity. Assessment of the practices among different population groups as well as different geographical locations thus has been a priority issue. The objective of this study is to assess the menstrual hygiene practices among the village women attending a Primary Health Centre of Sipahijala district, Tripura. Methods: The study was conducted among 141 village women of reproductive age group (15-49 years), visited Madhupur primary health centre, Sipahijala district, Tripura for some other health conditions. Unwilling individuals were excluded from the study. Data were collected using a pre-designed pre tested schedule by interviewing the participants for basic socio-demographic variables as well as questions related to hygienic practices during menstrual period. Data were analysed using IBM SPSS version 20 and presented using principles of descriptive statistics. Ethical clearance was obtained from Institutional Ethics Committee, Tripura Medical College. Results: Majority of the study subjects belonged to 21-30 years of age group (49.3%). Cloth was the major absorbent material (44.0%) followed by sanitary napkin (36.2%). 47.5% of the study subjects reused the material. Only 2.1% of the study subjects changed the material less than 2 times/day. More than 90% of the study subjects clean their private parts regularly. 66.0% of the study subjects disposed the material in dustbin. Conclusions: Majority of the participants were performing satisfactory menstrual hygienic practices. However, large scale analytical studies will be helpful to draw a definite conclusion about influence of sociodemographic factors on menstrual hygiene practices.